2018
DOI: 10.21836/pem20180401
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endocrine and metabolic responses to oral glucose test and combined glucose-insulin tests in horses

Abstract: Different diagnostic tests to determine the insulin sensitivity in horses are commonly used in veterinary practice. However, endocrine and metabolic responses provoked by physiological processes during the respective test procedures are not well described. In the present study, oral glucose tests (OGTs) and combined iv glucose-insulin tests (CGITs) were employed under standardized conditions. The OGTs and CGITs were performed in twelve healthy warmblood horses of different sex, age (15 ± 6.5 years), weight (56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…This study identified sustained increases in serum insulin and glucose concentrations following IA TA administration in horses without evidence of insulin dysregulation. Mean and peak serum insulin concentrations did not exceed levels considered safe when conducting an OST test, 9,15 suggesting that IA TA injection at this dose is unlikely to result in laminitis. However, insulin concentrations stayed elevated for 48 h, whereas insulin concentration is expected to return to normal within 180 min during an OST test.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This study identified sustained increases in serum insulin and glucose concentrations following IA TA administration in horses without evidence of insulin dysregulation. Mean and peak serum insulin concentrations did not exceed levels considered safe when conducting an OST test, 9,15 suggesting that IA TA injection at this dose is unlikely to result in laminitis. However, insulin concentrations stayed elevated for 48 h, whereas insulin concentration is expected to return to normal within 180 min during an OST test.…”
Section: Discussionmentioning
confidence: 84%
“…The average peak blood insulin concentration post IA TA injection was less than 45 μIU/mL, a concentration considered in the normal range for horses undergoing an OST, in all but one instance.Veterinarians and owners frequently discuss the risk of laminitis when administering IA corticosteroids for treatment of joint disease.This study identified sustained increases in serum insulin and glucose concentrations following IA TA administration in horses without evidence of insulin dysregulation. Mean and peak serum insulin concentrations did not exceed levels considered safe when conducting an OST test,9,15 suggesting that IA TA injection at this dose is unlikely to result in laminitis. However, insulin concentrations stayed elevated for 48 h, whereas insulin concentration is expected to return to normal within 180 min during an OST test.…”
mentioning
confidence: 85%